PENGARUH BAURAN PEMASARAN JASA TERHADAP PERSEPSI SISWA SMU PADA UNIVERSITAS SWASTA â€Xâ€ DI JAKARTA (SURVEY PADA SISWA SMU DI WILAYAH DKI JAKARTA) - Yunika Murdayanti; Purwanto Widodo (Jurnal Ilmiah Econosains, 2011)
Abstract The objective in this research is to test the influence of Marketing Service Mix 7 P based on different gender and different school to high school student perception at PTS â€œXâ€. Research methods of the research are survey method and are taken purposively sampling techniques with standard of 5% error. Respondent of this research are 305 student from all of high school student in Jakarta. Based on the type of school consist of 200 respondent from state high school and 105 respondent from private high school, and based on gender consist of 128 male respondent and 177 female respondent. The results of this research use Structural Equation Model (SEM) show that Product and Price have significantly influence to the high school perception in the partial test. The test based on gender show that only in the female gender tests indicate that Product, Promotion, and Lecturer have significantly influence to the high school perception. And based on the type of school, 1) the state high school results indicate that Product, Promotion, and Price have significantly influence to the high school perception and 2) the private high school results indicate that only Product has significantly influence to the high school perception. The conclusion is the variable Product have positive contribution and significantly influence to the high school perception for all variable tests and for suggestion, the effective promotion tools to introduce their school is the television. Keywords: product, price, place and promotion, physical evidence, lecturer and process, perception.